From Planetary Boundaries to national fair shares of the global safe operating space — How can the scales be bridged?. (September 2016) - Häyhä, Tiina; Lucas, Paul L.; van Vuuren, Detlef P.; Cornell, Sarah E.; Hoff, Holger
Highlights: Policy demand is growing for operationalizing the Planetary Boundaries (PB) concept. We have developed a conceptual framework to translate PBs to national scale. We distinguish the biophysical, socio-economic and ethical dimensions. We identify tools and approaches to address the dimensions and bridge scales. We evaluate previous PB application studies in the light of our framework. Abstract: The planetary boundaries framework proposes quantitative global limits to the anthropogenic perturbation of crucial Earth system processes, and thus marks out a planetary safe operating space for human activities. Yet, decisions regarding resource use and emissions are mostly made at less aggregated scales, by national and sub-national governments, businesses, and other local actors. To operationalize the planetary boundaries concept, the boundaries need to be translated into and aligned with targets that are relevant at these decision-making scales. In this paper, we develop a framework that addresses the biophysical, socio-economic, and ethical dimensions of bridging across scales, to provide a consistently applicable approach for translating the planetary boundaries into national-level fair shares of Earth's safe operating space. We discuss our findings in the context of previous studies and their implications for future analyses and policymaking. In this way, we link the planetary boundaries framework to widely-applied operational and policy concepts for more robust strong sustainability decision-making.